PROPER MEASUREMENT AND ASSESSMENT OF LEARNING IN ONLINE LEARNING - Sugeng Hariyanto; Iwan Setiawan; Khasanah Samsudin (LP2M IAI Al-Khairat Pamekasan, 2026)
Measuring and assessing online learning is very important to study because online learning with its advantages and disadvantages is a form of learning that is currently widely used. The purpose of writing this article is to find out what platforms are appropriate to use for online learning assessment. This article was written using a simple qualitative descriptive and literature study method by reviewing several related literature. The data collection location at SIT Ibnu Abbas Cikarang was 35 teachers. Data collection was done using random sampling. The results of this research are measurements and assessments of online learning at SIT Ibnu Abbas Cikarang using several platforms, namely Quiziz, Google Form, Kahoor, and Wordwal. Quiziz is one of the most interesting platforms compared to others. The percentage of results comparing teachers' perceptions of good and interesting platforms is, for Google Form an average of 31.43%, an average of 51.43% for Quizizz, an average of 2.86% for Kahoo,t and an average of 8.57% for Wardwall. This article concludes that Quiziz is a good and interesting online learning and assessment medium.